Ethnobotany of wild mushrooms in the Maamora Forest region, Northwestern Morocco - Fellaki, Anas; Rochdi , Atmane; ElYacoubi , Houda; ElYamani, Asmaa; Abourouh, Mohamed (Ethnobotany Research and Applications, 2025)
Background: Wild mushrooms are a very important source of food, medicines as well as other biologically active compounds, and are studied intensively worldwide. The Maamora Forest is an area where the traditional use of mushrooms is still preserved, offering a unique opportunity to explore these cultural practices. The present research aims to document the rich and poorly known traditional uses of wild mushrooms from this area. Methods: Our ethnomycological survey was carried out using a semi-structured questionnaire with 236 participants. The data were analyzed using statistical methods, including the Chi-square () test, Multiple Correspondence Analysis (MCA), and Non-Metric Multidimensional Scaling (nMDS). Ethnobotanical indices such as Cultural Importance Index (CI), Fidelity Level (FL), and Informant Consensus Factor (ICF) were also employed. Results: CI focuses primarily on income rather than food and ethnomedicine. Six wild edible mushrooms are used, mostly in their fresh form, as a substitute for meat and incorporated into various traditional Moroccan dishes. This study identified six wild medicinal mushrooms with varying FL and seven use categories, including anti-cancer, all with high ICF values. Two cases of mushroom poisoning in the study area were recorded. MCA showed the relationships among all tested variables, while nMDS highlighted the correlations between the distribution of wild mushrooms and their respective cantons. Conclusions: Our ethnomycological survey brought to light methods of conservation, preparation, and application of wild mushrooms that had never been recorded in previous research. contributing to the preservation of local knowledge and supporting future studies in nutrition, pharmacology, and biodiversity conservation. Keywords: Ethnomycology, Wild Edible Mushrooms, Medicinal Mushrooms, Poisoning Mushrooms, Maamora Forest